The Design Body Support Pillow Prevent and Reduce Pressure Ulcers - Anam, Agus Khoirul; Lestari, Jihan (Health Gate, 2024)
Patients with a long duration of bed rest have a potential risk of impaired skin integrity due to prolonged pressure that can lead to the appearance of decubitus. One alternative to prevent decubitus is by giving mobilization over the bed that is tilt right and left every 2 hours with an angle of 30° with a foam pillow as a buffer in bed. This study aims to design a right and left tilt body support pillow as an effort to prevent and reduce the risk of decubitus ulcers in bed rest patients. The method used in this study is Research and Development (R&D) with ADDIE method which consists of five stages which include analysis, design, development, implementation and evaluation. This study was conducted at Mitra Medika Clinic in Blitar Regency with 6 participants and 3 media experts. The results of this study show that the value of product feasibility from expert validators is 98% and from participants is 99%. The results showed the product has met the criteria very feasible based on the assessment of the participants. It is expected that this product can help nurses in maintaining the right and left tilt position as an effort to prevent and reduce the risk of decubitus ulcers in bed rest patients. Keywords: Pressure Ulcer, Body Support Pillow, Design